1994
DOI: 10.1523/jneurosci.14-08-04716.1994
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the NG2 chondroitin-sulfate proteoglycan after brain injury

Abstract: Injury to the adult mammalian CNS results in reactive changes among the glial cells surrounding the site of damage. Recently, an unusual class of glial cells has been identified within the intact adult rat cerebellum on the basis of the expression of the NG2 chondroitin-sulfate proteoglycan (Levine and Card, 1987). To determine whether the cells that express the NG2 proteoglycan show reactive changes after injury, small puncture lesions were made into the cerebelli of adult rats, and changes among astrocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
292
5
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(334 citation statements)
references
References 29 publications
29
292
5
8
Order By: Relevance
“…The NG2 proteoglycan is increased after CNS injury by oligodendrocyte precursor cells (Levine, 1994;Rhodes et al, 2006), phosphacan is upregulated within glial scars (McKeon, et al, 1995), and phosphacan, brevican, versican, and neurocan are all produced within the injured spinal cord (Jones, et al, 2003a). Chondroitin sulfate proteoglycans are found in the brain after stab wound (Fitch and Silver, 1997a), in the spinal cord after injury to the dorsal root (Pindzola et al, 1993), and in the spinal cord following injury (Fitch and Silver, 1997a;Jones, et al, 2003a;Jones et al, 2003b).…”
Section: Molecules Within the Glial Scar Contribute To Regenerative Fmentioning
confidence: 99%
“…The NG2 proteoglycan is increased after CNS injury by oligodendrocyte precursor cells (Levine, 1994;Rhodes et al, 2006), phosphacan is upregulated within glial scars (McKeon, et al, 1995), and phosphacan, brevican, versican, and neurocan are all produced within the injured spinal cord (Jones, et al, 2003a). Chondroitin sulfate proteoglycans are found in the brain after stab wound (Fitch and Silver, 1997a), in the spinal cord after injury to the dorsal root (Pindzola et al, 1993), and in the spinal cord following injury (Fitch and Silver, 1997a;Jones, et al, 2003a;Jones et al, 2003b).…”
Section: Molecules Within the Glial Scar Contribute To Regenerative Fmentioning
confidence: 99%
“…During neural development, CSPGs regulate axon growth and pathfinding (Snow et al, 1990;Jhaveri, 1993). After injury in the adult, they are enriched in scar tissues (McKeon et al, 1991;Levine, 1994;Lemons et al, 1999;Properzi et al, 2005), in which they contribute to hampering axon regeneration (Davies et al, 1997;Moon et al, 2001;Bradbury et al, 2002;Grimpe and Silver, 2002;Jones and Tuszynski, 2002) or compensatory sprouting (Tropea et al, 2003). In addition, several studies have highlighted their role in controlling structural plasticity in the absence of injury (Brakebusch et al, 2002;Pizzorusso et al, 2002;Miyata et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Tsiperson et al (2015) also demonstrated that following demyelination by cuprizone, an increase in PDGFR␣ progenitors was observed in wild mice as a result of increased DNA synthesis and cell proliferation. According to Decker et al (2002), cytokines and growth factors released either from widespread inflammatory and glial cells (Levine, 1994) or from damaged axons after demyelination (Di Bello et al, 1999), induce OPCs to reenter the cell cycle after demyelination.…”
Section: Discussionmentioning
confidence: 99%